2005
DOI: 10.33336/aik.93631
|View full text |Cite
|
Sign up to set email alerts
|

Liiketalousinnovaatioiden keksiminen on myös kognitiivinen prosessi

Abstract: Luovuus ja keksiminen on perinteisesti liitetty tieteeseen, teknologiaan ja taiteeseen. Kuitenkin myös liiketaloudellisessa toimintaympäristössä on käyttöä luovuudelle. Siksi taloutta kutsutaan nykyisin innovaatiotaloudeksi. Informaatiolla ja tiedolla ei kuitenkaan ole merkitystä, jos niitä ei osata soveltaa innovaatioprosessissa. Innovatiiviset yritykset ja innovatiiviset henkilöt keskittyvät enemmän tulevaisuuteen kuin menneeseen ja tällöin on sitouduttu luopumaan vanhoista uskomuksista, teorioista ja toimin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…Without a doubt, inventing something new is perhaps the highest degree of human mental ability and the clearest manifestation of human rationality. The cognitive-historical studies have shown that often scientific-, technological-and business breakthrough starts from unexpected perceptions ( Suomala et al, 2006 ; Thagard, 2009 ). Warren’s case is a good example of this.…”
Section: The Heuristics and Biases Approachmentioning
confidence: 99%
“…Without a doubt, inventing something new is perhaps the highest degree of human mental ability and the clearest manifestation of human rationality. The cognitive-historical studies have shown that often scientific-, technological-and business breakthrough starts from unexpected perceptions ( Suomala et al, 2006 ; Thagard, 2009 ). Warren’s case is a good example of this.…”
Section: The Heuristics and Biases Approachmentioning
confidence: 99%